PENGARUH BRAND IMAGE, KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN - Susanti, Irma Yusniar; Tjahjono, Endro; Nasution, Ute Chairuz (Jurnal Dinamika Administrasi Bisnis, 2015)
Competition between adventure product is very tight, from local brands to international brands all trying to get a place in hearts of customers. Many basic influence consumers to buy a product, including of brand image, quality product, and price. This research was quantitative methode with multiple linear regression analysis. The purpose is to determine the influence of brand image, quality product, and price of the purchase decision. While the price variable is more dominant influence on purchase decisions of the brand image and quality product. Looking at the result of the research, the writter suggest that people see a product not only of price but also on the quality of its product, so that it can be satisfaction when bought with a longer life. Whereas for the brand image factor could be done when if the previous factors have been met. For the future research is expected to further improve the quality of test, so this research has better. Â Keywords : brand image, quality product, and the price of purchase decision.